Agarose based large molecular systems: Synthesis of fluorescent aromatic agarose amino acid nano-conjugates – their pH-stimulated structural variations and interactions with BSA. (8th September 2017) - Sharma, Atul K.; Chudasama, Nishith A.; Prasad, Kamalesh; Siddhanta, A.K.
Abstract: Two new nano-sized fluorescent 6-amino agarose naphthalic acid half ester derivatives were synthesized (ca.60% yields) employing 1, 8- and 2, 3-naphthalic acid anhydrides (1, 8-AANE, and 2, 3-AANE respectively). These large nano molecular frameworks (DLS 3 & 100 nm, and 3 & 152 nm respectively) contains amino, naphthalate half-ester carboxyl groups at the C-6 positions of the 1, 3-β-D-galactopyranose moieties of the agarose backbone (overall DS 0.94). Structures were characterized (FT-IR, and 13 C & 1 H NMR spectrometries). These materials mimicked a large protein conjugate (GPC 123, and 108 kDa) exhibiting pH-responsive conformational variations (optical rotatory dispersion), offering a mixed solubility pattern like a soluble random coil (pH 4–10), and precipitate (pH 2) formation. With bovine serum albumin 1, 8- and 2, 3-AANE showed complexation, and decomplexation at pH 5.2, and 6.8 respectively. However, they showed decomplexation, and complexation respectively at pH 10 (circular dichroism). These fluorogenic systems may be of prospective utility as chiral sensors and in the realms demanding the virtues of preferential protein bindings. Graphical abstract: Graphical abstract of structural transformation and interaction with BSA of AA- NPs at different pH medium. Highlights: Synthesis of nano-sized 6-aminoagarose naphthalate half-ester derivatives (AANEs). AANEs exhibited protein-like pH-responsive behavior. Zeta-potential measurements showed no isoelectric points of AANEs. AANEs exhibited pH-specific single strand and aggregate formation (ORD). AANEs exhibited pH-dependent associative interactions with bovine serum albumin.